KAJIAN LONGSOR AKIBAT GEMPA DI NAGARI TANDIKEK KECAMATAN PARTAMUAN KABUPATEN PADANG PARIAMAN SUMATERA BARAT, INDONESIA - Amrizal Saidi; Isril Berd; R Har (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2011)
Earthquacke on 30th of September 2009 in West Sumatra had ruined Padang Pariaman, Agam, and Padang city districts. The damage was not only caused by the earthquake itself but also due to the landsliding following the earthquake, such as in Tandikek. Hundreds of people, houses, buildings, schools, as well as agricultural land (ricefield and dryland farming) were burried in Lubuk Laweh, Kepala Koto and Cumanak. This research was conducted by employing survey method and by observing the phenomenon of tuff pumice on how it was affected by earthquake and water. Then, soil characteristics were analysed based on soil physical data from previous research. Several soil characteristics analysed were soil texture, bulk density, structure and depth of solum, organic matter content, and permeability. Land characteristics were determined through field visit. Some land condition being observed was slope (percentage and length), stone exposed, soil water depth, and land use. Additionally, besides from field visit, the data were also obtained from topography and morphology maps derived from Google Earth. Rainfall data (monthly and annually) were collected from several nearby meteorology stations. Analyses for degree of landsliding risks for an area were used soil and land characteristics criteria causing landsliding. Based on field visit, it was seen that the research area was still susceptible to landsliding. This was due to the parent materials of the soil deriving from tuff pumice which is crumb structure and loamy texture on the top layer. Climate, especially annual rainfall in study site was high enough (approximately 4322 mm) which was evently distributed all year long without dry month. Slope of the area was > 45%, especially areas hit by landsliding. Land use was not based on soil conservation rule, such as coconut and arenga pinneca, and other mixed trees were planted on the area having > 45% slope. The results of the soil characteristic analyses showed that HARKAT interval of lansliding threat was 13 and land characteristics showed 20. Summation of HARKAT values from soil and land characteristics was 33. This number showed that the study site had high degree of landsliding risk. The possibility of areas would be hit by lansliding were Partamuan, Koto Timur, Sungai Geringging, and around Maninjau lake.Keywords : earthquake, soil and land characteristics, tuff pumice, wet tropical